If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + b) + -3(4 + -3c) = 5b + 6x Reorder the terms: 4(b + 2x) + -3(4 + -3c) = 5b + 6x (b * 4 + 2x * 4) + -3(4 + -3c) = 5b + 6x (4b + 8x) + -3(4 + -3c) = 5b + 6x 4b + 8x + (4 * -3 + -3c * -3) = 5b + 6x 4b + 8x + (-12 + 9c) = 5b + 6x Reorder the terms: -12 + 4b + 9c + 8x = 5b + 6x Solving -12 + 4b + 9c + 8x = 5b + 6x Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. -12 + 4b + 9c + -5b + 8x = 5b + -5b + 6x Reorder the terms: -12 + 4b + -5b + 9c + 8x = 5b + -5b + 6x Combine like terms: 4b + -5b = -1b -12 + -1b + 9c + 8x = 5b + -5b + 6x Combine like terms: 5b + -5b = 0 -12 + -1b + 9c + 8x = 0 + 6x -12 + -1b + 9c + 8x = 6x Add '12' to each side of the equation. -12 + -1b + 9c + 12 + 8x = 12 + 6x Reorder the terms: -12 + 12 + -1b + 9c + 8x = 12 + 6x Combine like terms: -12 + 12 = 0 0 + -1b + 9c + 8x = 12 + 6x -1b + 9c + 8x = 12 + 6x Add '-9c' to each side of the equation. -1b + 9c + -9c + 8x = 12 + -9c + 6x Combine like terms: 9c + -9c = 0 -1b + 0 + 8x = 12 + -9c + 6x -1b + 8x = 12 + -9c + 6x Add '-8x' to each side of the equation. -1b + 8x + -8x = 12 + -9c + 6x + -8x Combine like terms: 8x + -8x = 0 -1b + 0 = 12 + -9c + 6x + -8x -1b = 12 + -9c + 6x + -8x Combine like terms: 6x + -8x = -2x -1b = 12 + -9c + -2x Divide each side by '-1'. b = -12 + 9c + 2x Simplifying b = -12 + 9c + 2x
| (2x-3)/(-1)=(1-4x)/2 | | 27y-18= | | 5r^2-22r+21=0 | | 2x-1/21=x-5/24 | | 5n+5=2p | | 50=3x+5x | | 180=2(4y-15)+7 | | 7(t-8)+50=10t+14+2t | | 8n-6+1n+10= | | .1(40x)-1/2(16) | | 3(x-7)+2x=10 | | 3(x+2)=0.55(2x+3) | | 180x(2x+8)= | | X+.05=2.10 | | (-3g)-(-1)= | | 4u+9=69 | | 5q+14=72q | | 2q+375=857 | | 3(x+13)=7x-9 | | 7(t-8)+50=10t+15+2t | | 8e-(-2)=6 | | 4/9x^2=3 | | y-1/3=1/6 | | 9+5r+5r+2r= | | 30=1x-80 | | -1.4-2.7= | | 9(2x+3y)= | | 174=14.3*c*27 | | 4x-8=3y-15 | | 8h+20=69 | | 1-6(4-7x)=-23-3x | | 3(2x-5)-4x=5-4(7-x) |